2011
DOI: 10.1016/j.virol.2011.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Tat-mediated HIV-1 replication and neurotoxicity by novel GSK3-beta inhibitors

Abstract: The HIV-1 protein Tat is a critical regulator of viral transcription and has also been implicated as a mediator of HIV-1 induced neurotoxicity. Here using a high throughput screening assay, we identified the GSK-3 inhibitor 6BIO, as a Tat-dependent HIV-1 transcriptional inhibitor. Its ability to inhibit HIV-1 transcription was confirmed in TZM-bl cells, with an IC50 of 40 nM. Through screening 6BIO derivatives, we identified 6BIOder, which has a lower IC50 of 4 nM in primary macrophages and 0.5 nM in astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 98 publications
(111 reference statements)
0
38
1
Order By: Relevance
“…We used VEEV, since the 6BIOder compound was previously shown by our group to significantly inhibit viral replication (95). Quantification of previously obtained data (33,95) in Fig. 1B indicated that 18BIOder was effective in inhibiting Tat-dependent HIV-1 transcription (Ͼ75% inhibition) but ineffective in VEEV infection (no inhibition).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We used VEEV, since the 6BIOder compound was previously shown by our group to significantly inhibit viral replication (95). Quantification of previously obtained data (33,95) in Fig. 1B indicated that 18BIOder was effective in inhibiting Tat-dependent HIV-1 transcription (Ͼ75% inhibition) but ineffective in VEEV infection (no inhibition).…”
Section: Resultsmentioning
confidence: 99%
“…We previously identified the GSK-3␤ inhibitor 6BIO as a potent HIV-1 LTR transcriptional inhibitor by performing a high-throughput screen for Tat-dependent transcription inhibitors from LopacSigma-Aldrich (1,280 compounds) and Spectrum-Microsource (2,000 compounds) (33). In order to identify more potent 6BIO analogs, a Hit2Lead compound query based on chemical structure yielded 38 commercially available derivatives.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations